AGRICULTURAL TRACTOR: INFLUENCE TO GEAR SELECTION ON ENERGY DEMAND AND COSTS IN SUGARCANE TRANSSHIPMENT - Lopes, Arthur G. C.; Filho, Aldir C. Marques; Correia, Tiago P. Da S.; Firmino, Paulo C.; Silva, Paulo R. A. [UNESP] (FapUNIFESP (SciELO), 2023)
Sugarcane is one of Brazil's leading crops, and the transshipment harvesting operation represents a significant portion of operating costs. Among the primary machines used in harvesting is the tractor-transshipment set, with considerable energy demands. This study focused on evaluating the gear selection effect in an agricultural tractor on operational performance and costs during the sugarcane transshipment operation. The treatments consisted of four operational work gears at different engine speeds: r1 – 1150 rpm, r2 – 1230 rpm, r3 – 1360 rpm, and r4 – 1500 rpm on the engine. The analyzed variables were volumetric and specific fuel consumption, operational efficiency, and operational cost. The variables were adapted from ASABE (2011) methodology, and the data were submitted to parametric statistics and regression analysis. The rotation engine selection in tractors directly affected fuel consumption with positive angular coefficients and r2 between 0.92-0.96. Fuel consumption reduces by 37.5%, adopting 1150 rpm compared to 1500 rpm rotation. The highest rotation (1500 rpm - r4) increased the volumetric and productive fuel consumption, enabling savings up to reduced fuel cost by 1.08 US$ ha-1. Thus, training sugarcane transshipment operators is essential to optimize the production process efficiency and reduce costs.
Keywords: fuel consumption; gear scaling; optimization; productivity; Saccharum officinarum